(untitled) (Zaranie Śląskie, 2025)
This article is devoted to the egodocuments found in a private family archive in Karviná more than 60 years after Gustaw Morcinek’s death: postcards, so-called odkrytki, and photographs of the writer. The documents were addressed to Małgorzata Wiejowa, a member of the Karviná family, whom the writer referred to as ‘my dearest’ or ‘beloved’. The materials — made available for editing by Aleksandra Raszka, daughter of Morcinkowa Małgosia — had not been documented before. They give a complete picture of the writer’s relationship with his sister’s granddaughter and—perhaps above all—reveal Morcinek’s almost paternal attitude towards his beloved Małgosia.